Sosialisasi Membentuk Karakter Mandiri dan Jiwa Kewirausahaan Siswa SMAN 3 Sampang - Zulviar Anas; Faisol Faisol (Nusantara Mengabdi Kepada Negeri, 2024)
The cultivation of entrepreneurship at SMAN 3 Sampang is still very low, there are no entrepreneurship subjects in the learning process so that the entrepreneurial spirit of students and students is still lacking. In entrepreneurial values, there are several attitudes, one of which is the attitude of independence, the attitude of independence of students and female students is still low. This is indicated by the way students and female students complete their assignments, students and female students still depend on friends to complete their tasks. This service activity uses socialization methods and discussion and lecture methods using power points. Before carrying out community service the team made an application to the school. This community service activity aims to foster the entrepreneurial spirit of students at SMAN 3 Sampang Regency which includes aspects of the entrepreneurial spirit, obstacles and factors that influence students' entrepreneurial spirit. The presentation of socialization material regarding entrepreneurship and independence was understood by the students, and there was a question and answer session with the community service team